THE LIMIT OF TERM PERIODIZATION ON LEGISLATIVE ASSEMBLY OFFICIALS: A CONSTITUTIONAL DEMOCRACY PERSPECTIVE - Akbar, M. Sokhikhul; Jamil, Jamil (jfpublisher, 2022)
Regulations regarding the periodization of legislative candidate requirements who has re-election for being to be legislative officials are not regulated in detail. However, this issue can refer to Article 182 of Law No.7/2017. Therefore, the term of Legislative Assembly officials in the 1945 Constitution of the Republic Indonesia in Article 19-22B concerning the House of Representatives does not at all discuss about it. In addition, Law No. 7/2017 concerning General Elections does not also regulate about how many times a legislative candidate can serve in a legislative institution. Unfortunately, there have been four changes to Law No. 27/2009 on MD3, Law No.17/2014 on MD3, Law No. 18/2018 regarding the second amendment to Law No.17/2014 concerning MD3, and the last one to Law No.13/2019 concerning MD3, none of these regulations discusses the number of term periodization on Legislative Assembly Officials. This research used descriptive qualitative methods normatively with statute approach and conceptual approach. In addition, the type of this research is juridical-normative. The data collection in this research is the data obtained will be processed and described in the form of a logical and systematic description to describe the principle of balance in a law agreement and the principle of balance contained in the Partnership Agreement itself. After the amendment of 1945 Constitution, the limitation of the term periodization only focused on the term of executive or presidential. Long-term periodization caused a polemic in authority. Absolute authority will open up opportunities for arbitrariness and corruption. Therefore, it requires to limit the term periodization on legislative institution.